Acellular dermal matrix scaffolds coated with connective tissue growth factor accelerate diabetic wound healing by increasing fibronectin through PKC signalling pathway. (6th December 2017) - Yan, Wenxia; Liu, Hanping; Deng, Xiaoyuan; Jin, Ying; Wang, Ning; Chu, Jing
Abstract: The regional injection of connective tissue growth factor (CTGF) for diabetic wound healing requires multiple components and results in a substantial loss of its biological activity. Acellular dermal matrix (ADM) scaffolds are optimal candidates for delivering these factors to local ischaemic environments. In this study, we explored whether CTGF loaded on ADM scaffolds can enhance fibronectin (FN) expression to accelerate diabetic wound healing via the protein kinase C (PKC) signalling pathway. The performance of CTGF and CTGF + PKC inhibitor, which were loaded on ADM scaffolds to treat dorsal skin wounds in streptozotocin‐induced diabetic mice, was evaluated with naked ADM as a control. Wound closure showed that ADM scaffolds loaded with CTGF induced greater diabetic wound healing in the early stage of the wound in diabetic mice. Moreover, ADM scaffolds loaded with CTGF obviously increased the expression of FN both at the mRNA and protein levels, whereas the expression of FN was significantly reduced in the inhibitor group. Furthermore, the ADM + CTGF group, which produce FN, obviously promoted alpha‐smooth muscle actin and transforming growth factor‐beta expression and enhanced neovasculature and collagen synthesis at the wound sites. ADM scaffolds loaded with CTGF + PKC inhibitor delayed diabetic wound healing, indicating that FN expression was mediated by the PKC signalling pathway. Our findings offer new perspectives for the treatment of diabetic wound healing and suggest a rationale for the clinical evaluation of CTGF use in diabetic wound healing.